Keanekaragaman Burung Air di Lahan Basah Desa Sungai Rasau Kecamatan Bumi Makmur Kabupaten Tanah Laut - Mahrudin Mahrudin; Muhammad Arsyad (Program of Biology Education, Universitas Lambung Mangkurat, 2019)
Biodiversity in some region one local potential that must be maintained for survival in the ecosystem. Diversity of fauna that lives in certain habitats will keep the balance some ecosystem, one example is water bird live in the wetland region. Wetland set aside resources and rooms for this fauna keep survival and sustainability. South Borneo has a lot of wetlands, which one is Sungai Rasau village. In this region have various types of wetlands, that are mangrove, fishpond, estuary, lowlands river, swamp, and rice field. existence this wetland invited a lot of live fauna, some kind is water bird. The purpose of this research is to analyze a variety of water birds in wetland Sungai Rasau subdistrict Bumi Makmur district Tanah Laut. The kind of this research is descriptive research, where describe existence the kind of water bird in that region and that connection with surroundings, especially coast region, mangrove, and fishpond because those wetlands are the widest area in that region. The sampling use Line transek technique with observation IPA-Count. Result of the research show types of water bird was found are 21 species from 7 families, where 15 species at the coast, 17 species at mangrove, and 20 species at Fishpond. Index diversity is 1 < H’ < 3, with categories of diversity, was or abundant.